Assessment of the hand in cerebral palsy - Praveen Bhardwaj; S Raja Sabapathy (Indian Journal of Plastic Surgery)
Cerebral palsy is the musculoskeletal manifestation of a nonprogressive central nervous system lesion that usually occurs due to a perinatal insult to the brain. Though the cerebral insult is static the musculoskeletal pathology is progressive. Some patients with cerebral palsy whose hands are affected can be made better by surgery. The surgical procedures as such are not very technically demanding but the assessment, decision-making, and selecting the procedures for the given patient make this field challenging. When done well, the results are rewarding not only in terms of improvement in hand function but also in appearance and personal hygiene, which leads to better self-image and permits better acceptance in the society. This article focuses on the clinical examination, patient selection, and decision-making while managing these patients.